2021
DOI: 10.2166/wp.2021.167
|View full text |Cite
|
Sign up to set email alerts
|

Water policy and regional economic development: evidence from Henan province, China

Abstract: With the rapid advance of industrialization and urbanization and the intensified impact of global climate change, the contradiction between the global water shortage and economic growth has become prominent. This paper, taking Henan province as an example, analyzed the influence of water resource policy on regional economic growth through a calculable general equilibrium model and further discussed the relevant policy recommendations. The results showed that the improvement of water supply, water efficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
0
0
1
Order By: Relevance
“…The study concluded that structure adjustment and tech improvement have a positive impact, while the water pricing policies has a negative impact on economy. This is consistent with other studies [41].…”
Section: Comparison With Previous Studiessupporting
confidence: 94%
“…The study concluded that structure adjustment and tech improvement have a positive impact, while the water pricing policies has a negative impact on economy. This is consistent with other studies [41].…”
Section: Comparison With Previous Studiessupporting
confidence: 94%
“…遴选居于主导地位的水、 能源、 食物行业, 并确定其 间的核心关联 [11] ; 二是仿真优化中如何更好地兼顾 行业间的直接关联与循环经济系统中的间接影响 因素, 以实现关联效应的综合定量评估 [12] 。对于上 述问题, 一种可行的解决思路是借助网络分析方法 对相关行业的投入产出联系进行全局分析, 并将识 别出的关联特征刻画在经济数学模型中, 在完整的 "社会经济-资源环境" 系统中评价关联作用机制。 社会网络分析(Social Network Analysis, SNA) 是定性和定量研究社会行动者结构关系特征的一种 方 法 [13] , 而 可 计 算 一 般 均 衡(Computable General Equilibrium, CGE) 模型则是模拟经济主体行为与政 策措施的主流模型 [14] 。结合投入产出数据, 前者 常被用于行业网络整体结构、 社团类别、 个体联系 特征的分析, 以识别区域主导行业, 优化行业结构与 发展方式 [15][16][17] , 制定战略资源或产品的贸易策略 [18,19] 。 目前, SNA 已成为行业间水-能源-食物关联网络的 重要解析方法, 商品贸易隐含的资源流动网络 [20,21] 、 资源生产管理部门的交流合作网络 [22,23] 则是相关研 究者的主要分析对象。在 CGE 分析框架里, 全行业 投入产出与消费、 贸易、 储蓄、 投资、 征税、 转移支付 等经济活动形成统一的复杂关联系统, 通过市场均 衡机制, 诸如行业生产技术升级 [24] 、 要素供给变化 [25] 、 财税政策调整 [26] 等冲击的响应可被全方位测度。凭 借坚实的经济数学理论基础和量化开放式复杂系 统的优势, CGE 模型被视为水-能源-食物关联仿真 优化与决策支持的重要工具 [12,27] , 应用范围也已从 两部门局部的投入产出关联研究扩展至三部门及 更多元的关联系统研究 [28,29]…”
unclassified